Explaining rising caesarean section rates in urban Nepal: A mixed-methods study - Sulochana Dhakal Rai; Edwin van Teijlingen; Pramod R. Regmi; Juliet Wood; Ganesh Dangal; Keshar Bahadur Dhakal (PLoS ONE, 2025)
Introduction Caesarean section (CS) rates are rising in urban hospitals in Nepal. However, the reasons behind these rising rates are poorly understood. Therefore, this study explores factors contributing to rising CS rates in two urban hospitals as well as strategies to make rational use of CS. Methods This cross-sectional mixed-methods study was conducted in 2021 in two hospitals, one public hospital and one private one in Kathmandu. The quantitative part included a record-based study of 661 births (private hospital = 276 and public hospital = 385) for the fiscal year 2018/19. The qualitative part included semi-structured interviews with 14 health professionals (doctors, nurses & midwives) and five key informants from relevant organisations and four focus group discussions with pregnant women in antenatal clinics in two hospitals. Quantitative data were analysed using SPSS v28. Qualitative data were organised through NVivo v12 and thematically analysed. Results The overall CS rate was high (50.2%). The CS rate in the private hospital was almost double than that in the public hospital (68.5% vs. 37.1%). Previous CS was the leading indication for performing CS. Non-medical indications were maternal request (2.7%) and CS for non-specified reasons (5.7%). The odds of CS were significantly higher in the private hospital; women aged 25 years and above; having four or more antenatal clinic visits; breech presentation; urban residency; high caste; gestational age 37-40 weeks; spontaneous labour and no labour. Robson group 5 (13.9%) was the largest contributor to overall CS rate, followed by group 1 (13.4%), 2 (8.8%), 3 (4.4%) and 6 (2.9%). Similarly, the risk of undergoing CS was high in Robson groups 2, 5, 6, 7 and 9. The qualitative analysis yielded five key themes affecting rising rates: (1) medical factors (repeated CS, complicated referral cases and breech presentation); (2) socio-demographic factors (advanced age mother, precious baby and defensive CS); (3) financial factors (income for private hospitals); (4) non-medical factors (maternal request); and (5) health service-related factors (lack of awareness/midwives/resources, urban centralised health facilities and lack of appropriate policies and protocols). Four main strategies were identified to stem the rise of CS rates: (1) provide adequate resources to support care in labour and birth (midwives/trained staff & birthing centres); (2) raise awareness on risks and benefits mode of childbirth (antenatal education/counselling and public awareness); (3) reform CS policies/protocols; and (4) promote physiological birth. Conclusion The high CS rate in the private hospital reflects the medicalisation of childbirth, a public health issue which needs to be urgently addressed for the health benefits of both mother and baby. Multiple factors affecting rising CS rates were identified in urban hospitals. This study provides insights into factors affecting the rising CS rate and suggests that multiple strategies are required to stem the rise of CS rates and to make rational use of CS in urban hospitals.